Assessment of the vitamin A fortification of peanut butter on middle-income and low-income Filipino families and consumers in Metro Manila - Tugano, Maricar Segismundo (2003)
ABSTRACT The survey was conducted to assess the impact of vitamin A fortification of peanut butter on selected low-income and middle-income Filipino families in Metro Manila. There were 151 respondents, 80 (53%) represents the middle-income family and 71 (47%) represents the low-income family. Demographics and socio-economic status of respondents showed that middle-income families have a greater number of household members than the low-income household. On the average, the middle-income family exceeds the low-income family by two persons per household. Middle-income families (37.50%) spend P1,001-P1,500 for food while 43.66% of the low-income families spend the same amount. But 35% of the middle-income families can spend a higher amount. For both income groups, the top consumers of the peanut butter were the children with aged between 4-16 years old. On the average, most of the children can consume peanut butter 0.5-20 tablespoons per week. Taste was the top determinant in buying peanut butter, (65% for the middle-income group and 59% for the low-income group).Lily's and Lady's Choice were the most popular brands of peanut butter. 86.25% of the middle-income respondents know/heard about vitamin A while 67.61% from the low-income respondents. In terms of knowledge on vitamin A fortified foods, 85% knows/heard about vitamin A fortified foods and 81.69% from the low-income group. 97.50% of the middle-income respondents were willing to buy peanut butter fortified with vitamin A and 97.18% of the low-income respondents. The major source of information of the respondents was the television.